1999
DOI: 10.1111/j.1749-6632.1999.tb08477.x
|View full text |Cite
|
Sign up to set email alerts
|

The Placental/Umbilical Cord Blood Program of the New York Blood Center A Progress Report

Abstract: The transplantation of placental/umbilical cord blood (P/CB) has been used successfully to reconstitute bone marrow function in both related and unrelated recipients. We report here the experience of the New York Blood Center P/CB Program. Since its inception in 1992, over 400 unrelated transplants were supported between July 1993 and September 1997. Overall, event-free survival for all diagnoses and ages approached 0.45. Success and rapidity of engraftment correlated most strongly with the degree of human leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 15 publications
1
24
0
2
Order By: Relevance
“…26 For populations with a different racial background than the NW European one, we certainly need more donors, but these can for logistic reasons most efficiently be recruited via cord blood collection. 8 As we just discussed, one of our major weaknesses is that it takes too long before a donor is selected, tested and the pre-transplant work-up of the patient is completed. Figure 4a shows the ED search time span data.…”
Section: Opportunitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…26 For populations with a different racial background than the NW European one, we certainly need more donors, but these can for logistic reasons most efficiently be recruited via cord blood collection. 8 As we just discussed, one of our major weaknesses is that it takes too long before a donor is selected, tested and the pre-transplant work-up of the patient is completed. Figure 4a shows the ED search time span data.…”
Section: Opportunitiesmentioning
confidence: 99%
“…Many Cord Blood Banks have followed the example of the National Cord Blood Program of the NYBC (NCBP-NYBC) and make a special effort to store cord bloods from minority group donors, which are underrepresented in the registries. 8 This can have a major impact on the ability to provide stem cell transplants to patients from minority groups as illustrated in Table 3. In this table, the performances in the year 2002 of the NYBC and the National Marrow Donor Program (NMDP) are compared for their ability to provide stem cells to minority group patients.…”
Section: Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although colonyforming units (CFUs) are still present in cord blood even after 72 h, 2 cryopreservation within 24 h following delivery is recommended to guarantee an optimum output. 7 Another study demonstrated that cord blood units tolerated shipment of up to 48 h without a significant reduction of the cell number, viability or plating efficiency. 8 Quality parameters usually consist of the number of viable cells, CFU and sometimes the frequency of CD34 þ cells, [8][9][10] but the capacities of the isolated progenitor cells have not yet been an objective.…”
Section: Introductionmentioning
confidence: 99%